Increasing the energy efficiency of a building by thermal insulation to reduce the thermal load of the micro-combined cooling, heating and power system. (November 2021) - Paraschiv, Spiru; Paraschiv, Lizica Simona; Serban, Alexandru
Abstract: The paper analyzes the energy consumption of an energy-independent house in two different situations, namely when the exterior insulation is installed and, respectively, in its absence. The result of the analysis was used to assess the reduction of fuel consumption and greenhouse gas emissions of the auxiliary heating system, namely a biomass boiler. The home's heating system consists of a Stirling cogeneration system with biogas, which produces 3 kW of electricity and 9 kW of heat, and a 50 kW biomass boiler. The biomass boiler must provide the additional heat necessary to cover the consumption of the house when the Stirling engine is running and respectively ensure the coverage of the complete heat consumption of the building when the Stirling engine is in standby mode. The analysis showed that the installation of external insulation on the building walls will reduce energy consumption by 13%–16%, depending on the variation of the outside air temperature.